Systematic Literature Review: The Impact Of Football Events On Local Economy And Tourism Sector - Sinurat, Ridwan; Hadiwijaya Louk, Michael Johannes; Pujiati, Amin; Kuryanto, Mohammad Syaffruddin; Anam, Khairul; Harvianto, Yudo (UNIVERSITAS NEGERI MAKASSAR, 2025)
This systematic literature review examines the economic and tourism impacts of football events on local communities, aiming to synthesise empirical evidence, evaluate methodological approaches, and identify determinants of success or failure. Utilising the PRISMA framework, the study analysed 92 peer-reviewed articles published between 2000 and 2023 from databases including Scopus, Web of Science, and EBSCO host. Inclusion criteria prioritised empirical studies on international, regional, and domestic football events, while theoretical analyses and non-football sports events were excluded. Data extraction focused on variables such as event type, geographic context, and stakeholder governance, with quality assessment conducted via the Mixed Methods Appraisal Tool (MMAT). Thematic analysis revealed three key findings: (1) mega-events generate significant short-term economic gains (78% of studies), particularly in hospitality and transportation sectors, but long-term sustainability remains limited (34% of studies), often overshadowed by hidden costs like infrastructure debt; (2) stakeholder collaboration and inclusive governance enhance benefit distribution, as seen in Germany’s post-2006 World Cup tourism growth (+8% over five years); and (3) small-scale events demonstrate greater economic sustainability and community engagement compared to mega-events due to lower costs and localized participation. The study highlights disparities between developed and developing nations, where the latter experience higher short-term GDP growth (+15%) but face greater financial risks. These findings underscore the need for transparent cost-benefit frameworks, post-event audits, and prioritised investment in regional events. By integrating quantitative and qualitative insights, this review proposes a holistic model for optimising football events as tools for equitable and sustainable development.